Thermal characterization of granular sludges from biologic treatments and its application to the generation of biogas - Almeida, S. [UNESP]; Horta, E. F. [UNESP]; Castro, M. C. A. A. [UNESP]; Crespi, M. S. [UNESP]; Maintinguer, S. I. [UNESP] (Springer, 2019)
The application of granular sludge from biological treatment plants can become an economically and environmentally viable process as a renewable source of energy. It is available in most countries, and its application can diversify the local energy potential. However, in order to achieve such benefits and make possible the development of more efficient conversion processes, prior knowledge of the composition of these materials is essential. In this sense, samples of granular sludge were obtained from upflow anaerobic sludge blanket reactors for the treatment of: (1) poultry slaughterhouse waste (Tiete-SP); (2) poultry slaughterhouse waste (Pereiras-SP); (3) wastewater treatment plant (SAo Carlos-SP) and (4) a mix of sludges 1, 2 and 3. Biogas generation tests in anaerobic batch reactors fed with sodium acetate and glucose separately as carbon sources were performed with samples 1, 2, 3 and 4, at initial pH 7.0 and 30 degrees C. Characteristic decomposition profiles were observed in the granular sludge tested. The two poultry slaughterhouse waste (samples 1 and 2) presented higher proportions of organic substrate molecules for the methanogenesis than the sanitary sewage sludge (sample 3), thus facilitating the production of the highest biogas, as verified in the tests carried out. The thermal characterization of the samples was relevant to the methane generation tests demonstrating the potential for the generation of this fuel.
Keywords: Biogas; Methane; Organic matter; Thermal stability; Granular sludge